Professional Responsibility of Labor Subjects - Vodopianova, N; Gofman, O; Nikiforov, G; Chiker, V (KnE Life Sciences, 2018)
The problem of the labor subjects’ responsibility is a challenging issue in the unstable conditions of the nowadays world and business. Within the organizational context, the professional responsibility is a regulator of the performance of assigned duties at work places, a standard of compliance with a job position or with the corporate culture requirements. А.R. Luria noted that the labor is the conscious development product of a subject, which means that restricting an employee to a job position or corporate standards may impoverish both an organization and its members. In this regard, the corporate and professional responsibility may have different consequences of the manifestation of the subjective position in solving complicated production tasks. This study proposes an integrated analysis of the professional responsibility of the labor subjects through three interrelated contexts: personal, cultural and activity-related; depending on the intensity level of these components, the labor subjects have a different level of professional responsibility. The purpose of this study is to analyze the specific features of the professional responsibility of employees in a Russian construction company depending on the axiological and situational determinants (159 people, the average age of the respondents is 36 years). Results: 1. A methodology was developed and tested that allowed identifying the situational determinants of professional responsibility (conceptions of the organizational reality in three temporal loci - past, present and future). 2. The leading role of the cognitive component is confirmed in the formation of the managerial type of responsibility. It is proved that this responsibility component is largely determined by situational characteristics: the conceptions of the professional and personal resources of the collective and the assessment of organizational reality. 3. The types of professional responsibility and their determinants are defined. Thus, the representatives of the impulsive and executive types are ”responsibility objects” (personal context), the carriers of the egocentric culture of professional responsibility (cultural context) and the incoherence of temporal loci. As opposed to them, the managerial type of responsibility is determined by the internal personal orientation (is an active subject) taking responsibility not only for oneself, but also for others (includes others in the culture of professional responsibility), as well as the ability for strategic thinking (which is manifested in consideration, at the same time, for the professional and organizational aspects of the past, present and future in the activities). The results obtained make the understanding of the professional responsibility mechanisms wider, allow developing managerial technologies to provide the personnel quality taking into consideration the professional responsibility and its dynamic multilevel nature; empirically substantiated is the significance of the cognitive component of responsibility (cognitive and reflexive resources). Identified are positive and negative subjective assessments of organizational reality and their influence on the types of professional responsibility. Keywords: types of professional responsibility, relationship of responsibility components, determinants.